2017
DOI: 10.1007/s00011-017-1062-2
|View full text |Cite
|
Sign up to set email alerts
|

Secretory leukocyte protease inhibitor regulates human periodontal ligament cell production of pro-inflammatory cytokines

Abstract: ObjectiveRegulation of immune-like cell properties of periodontal ligament (PDL) cells is not understood. We investigate the importance of secretory leukocyte protease inhibitor (SLPI) for production of pro-inflammatory cytokines in human PDL cells.Materials and methodsPDL cells were isolated from teeth extracted for orthodontic reasons. Cellular location of SLPI was investigated by immunocytochemistry. Cytokine transcript and protein expression were assessed by quantitative real-time RT-PCR and Western blotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Protein levels of CXCL1 (d), CCL2 (e), and CCL5 (f) in supernatants of human periodontal fibroblasts exposed to F. nucleatum and/or constant tensile strain (CTS) at 1 day and 2 days, as analyzed by ELISA. Mean values and SEM (n = 9/group), *significant (p < 0.05) difference between groups CCL2, and CCL5 expressions in human periodontal cells [38][39][40][41][42]. By demonstrating that these chemokines are upregulated in response to microbial stimuli, these studies support our in vitro findings.…”
Section: Discussionsupporting
confidence: 84%
“…Protein levels of CXCL1 (d), CCL2 (e), and CCL5 (f) in supernatants of human periodontal fibroblasts exposed to F. nucleatum and/or constant tensile strain (CTS) at 1 day and 2 days, as analyzed by ELISA. Mean values and SEM (n = 9/group), *significant (p < 0.05) difference between groups CCL2, and CCL5 expressions in human periodontal cells [38][39][40][41][42]. By demonstrating that these chemokines are upregulated in response to microbial stimuli, these studies support our in vitro findings.…”
Section: Discussionsupporting
confidence: 84%
“…We have shown by immunocytochemistry and Western blot that PDL cells express SLPI, although PDL cells show much lower expression of the protein compared to HaCaT cells 17 . E coli LPS increases both IL‐6 and MCP‐1 mRNA in PDL cells, whereas it has no effect in HaCaT cells, and thus, expression levels of SLPI negatively correlate with pro‐inflammatory cytokine expression 17 . Knockdown of PDL cell SLPI gene activity by siRNA enhances both basal and LPS‐stimulated IL‐6 and MCP‐1 expression, providing further evidence that SLPI indeed is a negative regulator of PDL cell production of pro‐inflammatory cytokines 17 .…”
Section: Human Pdl Cells Express Slpi and Cellular Levels Of Slpi Negmentioning
confidence: 83%
“…Intracellular SLPI has been shown to translocate from cytoplasm to nucleus and interact with NF‐κB signaling in monocytes 68 . We have shown by immunocytochemistry and Western blot that PDL cells express SLPI, although PDL cells show much lower expression of the protein compared to HaCaT cells 17 . E coli LPS increases both IL‐6 and MCP‐1 mRNA in PDL cells, whereas it has no effect in HaCaT cells, and thus, expression levels of SLPI negatively correlate with pro‐inflammatory cytokine expression 17 .…”
Section: Human Pdl Cells Express Slpi and Cellular Levels Of Slpi Negmentioning
confidence: 90%
See 1 more Smart Citation
“…Although high levels of MMP-9 proteins were observed with or without LPS treatment, Slpi −/− BMEos showed augmented invasive activity upon stimulation, suggesting that MMP-9 augmentation is barely involved in the LPS-induced invasion of Slpi −/− BMEos. A recent study demonstrated that the knockdown of SLPI by siRNA upregulated the expression of monocyte chemotactic protein-1 in LPS-treated periodontal ligament cells ( 58 ). Our microarray data also showed that several genes of chemokines and chemokine receptors are expressed in both B6 and Slpi −/− BMEos (GSE87638).…”
Section: Discussionmentioning
confidence: 99%